A scoping review of the post-discharge care needs of babies requiring surgery in the first year of life. - Francesca Giulia Maraschin; Fidelis Jacklyn Adella; Shobhana Nagraj (PLOS Global Public Health)
Congenital anomalies are among the leading causes of under-5 mortality, predominantly impacting low- and middle-income countries (LMICs). A particularly vulnerable group are babies with congenital disorders requiring surgery in their first year. Addressing this is crucial to meet SDG-3, necessitating targeted efforts. Post-discharge, these infants have various care needs provided by caregivers, yet literature on these needs is scant. Our scoping review aimed to identify the complex care needs of babies post-surgery for critical congenital cardiac conditions and non-cardiac conditions. Employing the Joanna Briggs Institute's methodological framework for scoping reviews we searched Pubmed, EMBASE, CINAHL, PsychINFO, and Web of Science databases. Search terms included i) specific congenital conditions (informed by the literature and surgeons in the field), ii) post-discharge care, and iii) newborns/infants. English papers published between 2002-2022 were included. Findings were summarised using a narrative synthesis. Searches yielded a total of 10,278 papers, with 40 meeting inclusion criteria. 80% of studies were conducted in High-Income Countries (HICs). Complex care needs were shared between cardiac and non-cardiac congenital conditions. Major themes identified included 1. Monitoring, 2. Feeding, and 3. Specific care needs. Sub-themes included monitoring (oxygen, weight, oral intake), additional supervision, general feeding, assistive feeding, condition-specific practices e.g., stoma care, and general care. The post-discharge period poses a challenge for caregivers of babies requiring surgery within the first year of life. This is particularly the case for caregivers in LMICs where access to surgical care is challenging and imposes a financial burden. Parents need to be prepared to manage feeding, monitoring, and specific care needs for their infants before hospital discharge and require subsequent support in the community. Despite the burden of congenital anomalies occurring in LMICs, most of the literature is HIC-based. More research of this nature is essential to guide families caring for their infants post-surgical care.